Prevalence of septal deviation in newborns: an institutional based cross sectional study - Jyoti, Deep; Sharma, Pallvi; Jamwal, Ashu; ., Arti (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Deviated nasal septum (DNS) is a common condition with various factors affecting its occurrence. The study was aimed to find the prevalence of DNS in newborns. Methods: The present study was a cross sectional study conducted in the SMGS hospital, GMC Jammu. A sample size of 200 newborns, less than 7 days of age were included in the study. 200 newborns in the postnatal wards were examined in the present cross-section observational study including the age ranging from 1 day to 5 days. Results: Prevalence of DNS in the present study was 29%. 103 babies were born to the primipara mothers out of which 39 (37.86%) had DNS while only 19 (19.58%) out of 97 babies born to the multipara mothers had the DNS. The newborns with higher birth weight had higher incidence of having DNS. 41.17% of the newborns with weight of >3 kg had DNS as compared to those in 2 to 2.5 kg group (17.28%) and <2 kg group (11.76%). Conclusions: DNS is a common finding since birth which may persist in later life. Routine examination of the newborns specifically regarding the nose should be done to detect the septal deviations at earliest so that active intervention can be done when required.